Fluid driven rotary atomiser for controlled droplet application of herbicides. - Craig, I. P. S. (Cranfield University, 1991)
Handheld electrically driven spinning disc atomisers are capable of applying pesticides more efficiently than with hydraulic nozzles, because the narrower droplet spectra they produce leads to reduced drift and wastage of chemical. Despite these savings however, farmers are frequently reluctant to use such methods because of poor reliability, and high maintenance costs of the electrical drive systems. This research has therefore examined an alternative drive system using a jet of the pesticide fluid to power the atomiser. Experiments have been carried out to increase understanding of the processes involved, with the aim of producing an optimum design suitable for mounting to a knapsack sprayer. The fluid drive mechanism is comparable to that of a Pelton Wheel; driving torque arises from a change in momentum of a fluid jet as it strikes the inside of a cup causing it to rotate. The fluid is emitted from grooves and teeth to form ligaments which produce uniform droplets. Peripheral distribution of fluid is made uniform by a series of slotted weirs on the inside wall of the cup. Form and size of various components including the nozzle, bearing, cup and atomising disc have been investigated. The requirement for low flowrate necessitates the use of a small nozzle with filter. Supply pressure available from hand- pressurised knapsack sprayers is also restricted. Available input energy is therefore limited, requiring that all the processes leading up to atomisation are as efficient as possible. Rotational speed is a function of jet velocity, mass flowrate, inner and outer cup radius, and bearing frictional torque. A simple computer model has been developed to predict the effects of changing these parameters. Radial exit velocity of the fluid has been derived from a consideration of the viscous forces to which thin fluid layers are subject during centrifugal acceleration upon rotating surfaces. This has enabled undisturbed ligament radius to be calculated, and has therefore provided a satisfactory method for the prediction of dropsize. Spectral and deposit characteristics are satisfactory for CDA herbicide application with water based formulations, although antifoam agent is required for formulations containing surfactant. Typical average droplet size for an operating pressure of 3 bar is 250μm, and optimum swath width is 1.2m for an intended application rate of 30 to 40 litres per hectare.
Keywords: drive system; fluid drive mechanism; nozzle; bearing; cup; atomising disc